THE ROLE OF OPERATIONAL MANAGEMENT AND DIGITALIZATION IN IMPROVING SHARIA INSURANCE SERVICES - Yudi Paruhum; M. Auliyah Al Ghazali ZA; Nurhayati Harahap (Yayasan Amanah Nur Aman, 2026)
This study was conducted to determine the role of operational management and digitalization in improving Sharia insurance services. The increasingly advanced development of digital technology requires Sharia insurance companies to improve service quality to make it faster, more effective, and easier for the public to use. However, several obstacles remain in implementation, such as operational system readiness, human resource quality, and customer data security in digital services. This study used a qualitative method with a descriptive approach. Data were obtained through observation, interviews, and literature review related to operational management, digitalization, and Sharia insurance services. Data analysis was conducted using descriptive qualitative techniques by collecting, compiling, and analyzing data obtained during the study. The results show that operational management plays a crucial role in improving service quality through work system management, service quality enhancement, and human resource management. Furthermore, digitalization has a positive impact on Sharia insurance services, such as facilitating service access, accelerating service processes, and increasing customer satisfaction. However, the implementation of digitalization still faces several obstacles, such as a lack of public understanding of digital services and data security risks. Based on the research findings, it can be concluded that operational management and digitalization have a mutually supportive relationship in improving the quality of Sharia insurance services. Therefore, Sharia insurance companies need to continuously improve their operational systems, human resource quality, and digital service security to optimize customer service.